Back to Kyoto? US Participation and the Linkage between R&D and Climate Cooperation - Barbara Buchner; Carlo Carraro; Igor Cersosimo; Carmen Marchiori (Center for Economic Studies and ifo Institute (CESifo), 2002)
The US decision not to ratify the Kyoto Protocol and the recent outcomes of the Bonn and Marrakech Conferences of the Parties drastically reduces the effectiveness of the Kyoto Protocol in controlling GHG emissions. The reason is not only the reduced emission abatement in the US, but also the spillover effects on technology and countries' relative bargaining power induced by the US decision. Therefore, it is crucial to analyse whether an incentive strategy exists that could induce the US to revise their decision and to comply with the Kyoto commitments. One solution, occasionally proposed in the literature and in actual policymaking, is to link negotiations on climate change control with decisions concerning international R&D cooperation. This paper explores this idea by analysing on the one hand the incentives for EU, Japan and Russia to adopt this strategy, and on the other hand the incentives for the US to join a coalition which cooperates both on climate change control and on technological innovation. The extended regime in which cooperation takes place on both dimensions (GHG emissions and R&D) will be examined from the view point of countries' profitability and free-riding incentives. Finally, after having assessed the effectiveness and credibility of the issue linkage strategy, we explore the economic and environmental benefits of a new, recently proposed regime, which aims at achieving GHG emission control by enhancing cooperation on technological innovation and diffusion (without targets on emissions).
Keywords: C70; H00; H40; O30; 330; agreements; climate; incentives; negotiations; policy; technological change